Ultrasound and Heat Treatment and Its Potential to Reduce Fennel Allergenicity - Gordana Maravić-Vlahoviček; Mirela Marić; Marija Badanjak Sabolović; Suzana Rimac Brnčić (Foods, 2025)
Fennel (Foeniculum vulgare), a member of the Apiaceae family, is known for its culinary and medicinal uses, as well as its potential to cause allergic reactions. Thermal and nonthermal technologies are commonly applied during the production of fruit and vegetable-based products, which may contain allergenic proteins. Consequently, understanding how these processing treatments affect allergenicity is crucial for managing allergenic risks during manufacturing and for identifying technologies that can reduce the allergenic potential of the final products. Currently, there is limited information available on how thermal and ultrasonic processing methods affect the allergenic properties of fennel. The aim of this study was to investigate the effects of ultrasound and heat treatment on the in vitro immunoreactivity of protein extracts from fennel. After sonication and heat treatment, the protein extracts were analyzed by denaturing polyacrylamide gel electrophoresis, Western blot and enzyme-linked immunosorbent assay. All treatments altered the protein patterns of fennel and partially degraded proteins in the range of 15–80 kDa. In addition, all treatments reduced IgE binding, indicating lower allergenicity. Western blotting with IgE from fennel-allergic patients confirmed these effects. The ultrasound probe had the strongest effect, almost eliminating IgE reactivity for several allergens. Heat treatment reduced allergenicity by about 30%, while sonication showed a reduction of about 15% and lower. A larger sample size is needed to better understand the effects of these treatments and the differences in individual allergic responses.